Description and analysis of patients and outcomes following third‐time heart transplantation: An analysis of the United Network for Organ Sharing database from 1985 to 2017. Issue 3 (8th February 2019) - Bhalla, Sameer; Dubey, Gaurav K.; Basu, Sanjib; Kanangat, Sivadasan; Dobrescu, Cosmin; Nath, Dilip S.
Abstract: Background: Following second heart transplantation (HTx), some patients experience graft failure and require third‐time heart transplantation. Little data exist to guide decision‐making with regard to repeat retransplantation in older patients. Methods: We performed a retrospective cohort analysis of patients receiving a third HTx, as identified in the United Network for Organ Sharing (UNOS) database from 1985 to 2017. Results: The study cohort consisted of N = 60 patients, with an average age of 29 with a standard deviation of ±18 years. Overall survival for the cohort at 1, 5, and 10 years is 83%, 64%, and 44%, respectively. The rate of third‐time HTxs has steadily increased in all age groups. Patients older than 50 years now account for 18.3% of all third‐time HTxs. Although this group demonstrated longer average previous graft survival, after third HTx they demonstrate significantly poorer survival outcomes compared to third‐time HTx recipients younger than 21 ( P  = 0.05). Age over 50, BMI over 30, and diabetes were all found to be independent risk factors for decreased survival following third HTx. Conclusions: We describe trends in patients undergoing third HTx. We highlight subsets of such recipients who exhibit decreased survival.